Prevalence and Risk Factors Associated with Pterygium in Farmers: Cross-Sectional Study in Indonesia - Muhamad Rifqy Setyanto; Nendyah Roestijawati; Wahyudin Wahyudin; Zainuddin Zainuddin; Muhammad Iqbal Firdaus (Comprehensive Health Care, 2023)
Background: Pterygium is a multifactorial fibrovascular growth of the bulbi conjunctiva. Farmers are a profession that is prone to pterygium because they do a lot of outdoor activities and are exposed to the risk factors that cause pterygium. Objective: To determine the prevalence and risk factors for pterygium in farmer groups in Petir Village, Kalibagor District, Banyumas Regency.Methods: This research is an analytic observational study using a cross-sectional study approach. The sample of this research was 69 farmers in Petir Village, Kalibagor District, Banyumas who were selected by consecutive sampling method. Data collection by interview using a questionnaire, and pterygium examination using a pen light. Data analysis using prevalence ratio. Results: The results of this study indicate that the prevalence of pterygium in farmer groups in Petir Village, Kalibagor Banyumas District is 15.9%. The results of the prevalence ratio analysis showed the prevalence ratio values of heredity (RP = 1,200 and CI = 1,077 - 1,337), age (RP = 1,196 and CI = 1,076 - 1,330), sex (RP= 0.865 and CI = 0.722 - 1.037), length of working period (RP = 1,212 CI = 1,081- 1,357), duration of work (RP = 0.884 and CI = 0.665 - 1.175), use of personal protective equipment (RP = 1.016 and CI = 0.814 - 1.268).Conclusion: Heredity, age, and length of working period are risk factors for pterygium in farmer groups in Petir Village, Kalibagor District, Banyumas. Gender, duration of work, and use of personal protective equipment were not risk factors for pterygium in farmer groups in Petir Village, Kalibagor District, Banyumas. Keywords: pterygium, farmer, length of work periode